Economic analysis of routine neuromonitoring of recurrent laryngeal nerve in total thyroidectomy (2015)
ABSTRACT: Introduction: Thyroidectomy is a common surgery. Routine searching of the recurrent laryngeal nerve is the most important strategy to avoid palsy. Neuromonitoring has been recommended to decrease recurrent laryngeal nerve palsy. Objective: To assess if neuromonitoring of recurrent laryngeal nerve during thyroidectomy is cost-effective in a developing country. Materials and methods: We designed a decision analysis to assess the cost-effectiveness of recurrent laryngeal nerve neuromonitoring. For probabilities, we used data from a meta-analysis. Utility was measured using preference values. We considered direct costs. We conducted a deterministic and a probabilistic analysis. Results: We did not find differences in utility between arms. The frequency of recurrent laryngeal nerve injury was 1% in the neuromonitor group and 1.6% for the standard group. Thyroidectomy without monitoring was the less expensive alternative. The incremental cost-effectiveness ratio was COP$ 9,112,065. Conclusion: Routine neuromonitoring in total thyroidectomy with low risk of recurrent laryngeal nerve injury is neither cost-useful nor cost-effective in the Colombian health system.